Lidar odometry and mapping for Pioneer robot - Abdelhadi Bousaid; Betaimi youcef; Chouireb Fatima (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2023)
One of the most important problems to be solved in mobile robotics is the question of where the robot is, and what the world around it, looks like. This is called Simultaneous Localization and Mapping (SLAM) problem. In this thesis, we are interested in the SLAM system using the Lidar sensor as a perception tool. First, we start by providing an overview of Lidar-Based SLAM and its significance in autonomous robotic systems. After that, we delve into the detailed analysis of the Sick LMS5xx laser measurement sensor used in this work, including its operational principles, data reading capabilities, and configuration using the SOPAS Engineering Tool. Then, the thesis explores the implementation of SLAM using the Robot Operating System (ROS). It covers the installation and utilization of all necessary packages, providing a comprehensive guide on how to set up and run them. The effectiveness of the SLAM implementation is then evaluated through simulations and real-world experiments on real Pioneer-3DX mobile robot.
SPECIALTY: Embedded System